Physical Therapy Interventions for Post-Operative a Giant Femoral Tumor: A Case Report - Ihsan, Muammar; Yanti, Ni Komang Artini; Rahayu, Ni Luh Veni; Sagita, Ni Made Indri; Puriyanti, Ni Made Rika; Putri, Thania Dwitia; Adhitya, I Putu Gde Surya; Jeviana, Ariezta (Kinetic and Physiotherapy Comprehensive, 2022)
Background: Giant cell tumor (GCT) is a relatively rare type of primary benign bone tumor, characterized by multinucleated giant cells resembling osteoclasts. Treatment of GCT with intralesional resection and bone cement filling, especially in tumors that develop around the knee joint. After GCT surgery around the knee joint, in general, patients will experience several symptoms such as pain in the operating area and surrounding structures, limited range of motion, then symptoms that are quite worrying, namely related to the ability of knee function in the future. The role of physiotherapy after GCT surgery around the knee joint, especially the distal anterolateral part of the femur, was stated to be able to restore the functional ability of the knee without limitations. Case Description: A 24-year-old male employee of the laboratory analysis division of Udayana University Hospital was diagnosed with GCT in the distal right femur. The diagnosis was made on September 30, 2021, using a biopsy with bone, joint, and articular cartilage specimens of the distal right femur. The patient underwent intralesional resection surgery, bone cement filling, and internal fixation of the distal femur in November 2021. Postoperatively the patient complained of pain in the posterior and medial distal right thigh, as well as limitations when bending the right knee. In addition, the patient also admitted to having difficulty doing squat movements. Conclusion: Patients experienced an improvement in their symptoms after carrying out 7 physiotherapy sessions for 3 weeks. However, the patient still needs further exercise so that the walking pattern can show better development.